2008
DOI: 10.1097/fjc.0b013e318185fa3c
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Epoxide Hydrolase Inhibitors Reduce the Development of Atherosclerosis in Apolipoprotein E-Knockout Mouse Model

Abstract: In order to determine whether sEH inhibitors influence atherosclerotic lesion formation, we utilized an established murine model of accelerated atherogenesis, ApoE knockout (−/−) mice. The sEH inhibitor, 1-adamantan-3-(5-(2-(2-ethylethoxy)ethoxy)pentyl)urea (AEPU) was delivered in drinking water. All animals were fed an atherogenic diet while simultaneously infused with angiotensin II by osmotic minipump to induce atherosclerosis. In AEPU-treated animals, there was a 53% reduction in atherosclerotic lesions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 35 publications
4
111
0
Order By: Relevance
“…Therefore, considerable interest has arisen in developing methods to enhance the bioavailability of EETs by inhibiting sEH. As expected, inhibition of sEH prevents several cardiovascular diseases, including high blood pressure, cardiac fibrosis, inflammation, and atherosclerosis (16,19,24). Therefore, the enzyme activity of sEH appears to play an important role in the development of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, considerable interest has arisen in developing methods to enhance the bioavailability of EETs by inhibiting sEH. As expected, inhibition of sEH prevents several cardiovascular diseases, including high blood pressure, cardiac fibrosis, inflammation, and atherosclerosis (16,19,24). Therefore, the enzyme activity of sEH appears to play an important role in the development of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble epoxide hydrolase (sEH) metabolizes EETs to their corresponding dihydroxyeicosatrienoic acids, which limits the availability of EETs (16). Several models of atherosclerosis have suggested that inhibition of sEH, with an ensuing decrease in EET degradation, may attenuate atherosclerosis development and aneurysm formation (3,14,15,19,25). Treatment with sEH inhibitors also attenuated cardiohypertrophy in rats with angiotensin II treatment and in a murine model with transverse aortic constriction (21).…”
Section: In This Study We Found That Soluble Epoxide Hydrolase (Seh)mentioning
confidence: 99%
“…During preparation of this manuscript, Ulu et al reported that an s-EH inhibitor, AEPU, also reduced the development of atherosclerosis in Ang II-treated apoE-deficient mice, which is consistent with the present results. 16 However, they found that AEPU did not reduce the plasma cholesterol levels. It could be attributable to the compound specific activity or the animals' failure to develop hyperlipidemia in this study, which is rare in atherogenic diet-fed apoE-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…There has been great recent interest in the therapeutic potential of sEH inhibitors as novel antiinflammatories. sEH inhibitors or genetic disruption of sEH in mice reduces inflammation in models of endotoxin-induced pulmonary inflammation (22), ischemia-reperfusion injury (33,34), subarachnoid hemorrhage (35), and the murine ovalbumin model of asthma (36), and in more chronic models including atherogenic diet-induced fatty liver disease and adipose tissue (37) and atherosclerosis (38,39). In contrast, the expression and roles of epoxy-oxylipins during inflammatory resolution have not been investigated.…”
Section: Discussionmentioning
confidence: 99%